A comprehensive kinetics for p-xylene increment by isomerizing C8 aromatics over Pt/HZSM-5. (15th March 2023) - Hao, Juan; Feng, Peixi; Xin, Feng; Wang, Zhiping; Zhou, Zhenhuan; Bao, Di; Zhu, Zhenxing
Highlights: A comprehensive isomerization network of C8 aromatics including disproportionation and deethylation reactions is proposed. A set of reaction rates for the above network are established to suit pure o-xylene, pure m-xylene and industrial feeds. An appropriate operating condition is determined to heighten the productivity of p-xylene. Abstract: Isomerization of C8 aromatics is an indispensable process for industrial production of p-xylene, but there is still a lack of rigorous kinetics of this reacting system. In this paper, the experiments for isomerization of C8 aromatics over Pt/HZSM-5 have been carried out in an isothermal fixed bed reactor under a wide range of operating conditions to obtain the rate laws for isomerization, disproportionation and deethylation reactions. A detailed kinetic model is developed from experimental data to accurately describe the reacting system of C8 aromatics, and the apparent kinetic parameters are estimated by genetic algorithm and least square method. The kinetic model verified by fitting experimental data can well predict the reaction trends of o-xylene, m-xylene and industrial feeds to exhibit good feed adaptability. Therefore, this model will support reactor design and operation.